Employing Role play in teaching and learning: a case of Higher Education - Mabusela, Sewela; Adams, Jabu (South African Journal of Higher Education, 2016)
The article looked, at how an approach like role playing could be employed in higher education settings in order to give students an opportunity to practice and to apply knowledge they have learnt about Learners with Special Educational Needs (LSEN). The main objective of the research was to explore the feasibility of using role play as a strategy to integrate experiential learning activities in the classroom in order to develop skills for identifying ELSEN by students. The secondary objectives were to report students role playing experiences , together with advantages and difficulties of using this form of teaching mode within the tertiary environment , and finally to find out how role play could be enhanced. To this end a qualitative research was employed to bring this investigation to realisation and a questionnaire was administered to undergraduate students in the faulty of education. The results suggest that although students experienced the role play activity as pleasant and saw value in using it, there were however disadvantages associated with it.